Swimming prevents cell death of chondrocytes via PI3K/AKT pathway in an experimental model - Jiajia Qian; Peiru Zhao; Qi Xu; Weiwei Yang; Ren Cai (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Knee Osteoarthritis (KOA) is one of the main causes of disability in the elderly and with limited treatment options. Swimming was considered as an ideal form of non-surgical management of KOA. Nevertheless, the mechanism of swimming intervene OA remains unclear. ACLT induced OA model was often used to study the pathogenesis and treatment of OA. Thus, we evaluated the protective effect of swimming on KOA mouse and tried to explore the underlying mechanism. Methods Forty C57BL/6 mice were randomly divided into five groups: Blank group, ACLT group, ACLT + Swim group, Sham group and Sham + Swim group (n = 8). OA model was established by Anterior Cruciate Ligament Transection surgery (ACLT). After modeling, mice in ACLT + Swim and Sham + Swim groups were trained with a moderate swimming program, 5 d/week, for 6 weeks. HE and Safranin-O/fast staining, Immunohistochemistry, TUNEL assay and Western blot were used to detect the effect of swimming on pathological changes, cell death and the mechanism in KOA mouse. Results Swimming significantly enhanced CoII expression and suppressed ADAMTS5 expression in cartilage of KOA mouse, thus ameliorated KOA development. Apoptotic and autophagic processes were enhanced in OA cartilage, which might be caused by down-regulation of PI3K/AKT pathway; swimming could activate PI3K/AKT pathway and thus regulate apoptosis and autophagy processes of chondrocytes. Conclusion Swimming could prevent cell death of chondrocytes via PI3K/AKT pathways, thus delayed the progression of KOA in an experimental model.